Improved rejection prophylaxis with an initially intensified dosing regimen of enteric-coated mycophenolate sodium in de novo renal transplant recipients - Budde, Klemens; Tedesco-Silva, Helio; Arns, Wolfgang; Shoker, Ahmed; Zeier, Martin; Klinger, Marian; Rosales, Beatriz; Walker, Rowan; Prestele, Hans; Vaidya, Soniya; Kuypers, Dirk (Transplantation, 2011)
Background. - Approximately half of cyclosporine A-treated renal transplant recipients do not reach sufficient mycophenolic acid (MPA) exposure in the first weeks posttransplantation with standard MPA dosing regimens. - Methods. - Here, we present a prospectively planned meta-analysis of data from two 6-month parallel-run studies that evaluated the effect of an initially intensified versus standard dosing regimen of enteric-coated mycophenolate sodium (EC-MPS). Four hundred forty-one de novo renal transplant recipients were randomized (1:1) to intensified (2 weeks 2880 mg/d; subsequently 4 weeks 2160 mg/d; followed by 1440 mg/d) or standard (1440 mg/d) EC-MPS, with concomitant cyclosporine A treatment and steroids with or without anti-IL-2R induction. Primary endpoint was treatment failure (biopsy-proven acute rejection [BPAR], graft loss, or death) at month 6 posttransplantation. - Results. - Treatment failure rates were 17.4% in intensified and 22.4% in standard groups (P=0.110). The incidence of BPAR was 13.8% (intensified) vs. 19.3% (standard; P=0.034). A total of 80.5% (intensified) versus 39.0% (standard) of patients achieved 12 hr MPA-area under the curve more than 30 μg·hr/mL as early as day 3 posttransplant. Renal function, gastrointestinal symptom rating scores, and safety profiles were comparable between treatment groups. - Conclusion. - The initially intensified EC-MPS dosing regimen was associated with higher MPA exposure, significantly lower rate of BPAR, and comparable safety. However, the intensified regimen did not affect graft function or survival.